1988
DOI: 10.2307/3349987
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Health Services, and Health Status in Rural America

Abstract: Access to health services for everyone has been a major policy goal in the United States: inequitable access is assumed to lead to inequitable health status, particularly for low-income groups. A sophisticated model of the relation between poverty, health care needs, service use, and health outcomes is used to analyze cross-sectional data on 7,823 adults from 36 rural communities. Improved access and use are helpful, but evidence clearly indicates that combined health and social initiatives will be necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…For the prediction of the number of doctor's visits, a zero-inflated negative binomial model specification is used to account for the large number of individuals with no visits. 6 Although tobit specifications are often used to model the number of physician visits (Laroche 2000;LeClere et al 1994;Patrick et al 1988), the tobit model is designed for continuous, rather than count, variables. The count nature of the data would imply a Poisson distribution, although the necessary assumption for this specification that the mean is equal to the variance is violated by these data (mean = 1.295 variance = 4.820).…”
Section: Methodsmentioning
confidence: 99%
“…For the prediction of the number of doctor's visits, a zero-inflated negative binomial model specification is used to account for the large number of individuals with no visits. 6 Although tobit specifications are often used to model the number of physician visits (Laroche 2000;LeClere et al 1994;Patrick et al 1988), the tobit model is designed for continuous, rather than count, variables. The count nature of the data would imply a Poisson distribution, although the necessary assumption for this specification that the mean is equal to the variance is violated by these data (mean = 1.295 variance = 4.820).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire's access concepts and dimensions incorporated the principal components of the prevailing models of access of Andersen, Aday, the Institute of Medicine, and others (Aday and Andersen 1974; Andersen et al 1983; Institute of Medicine, Committee on Monitoring Access to Personal Health Care Services 1993). Survey items included many of the standard outpatient primary care access‐relevant questions from national periodic surveys like the BRFSS and the National Health Interview Survey (CDC 2005), previous regional surveys (Patrick et al 1988), and published studies (Penchansky and Thomas 1981), and included a few new items to address rarely queried access issues, for instance whether people perceived travel for outpatient care was generally difficult. The questionnaire also included measures of outcomes of care, specifically people's satisfaction with various aspects of the care they received and indicators of its quality as reflected by the clinical preventive health care services recommended for their age and gender (AHRQ 2004) they had, or had not, received.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that an adequate primary care physician supply correlates with a variety of positive population health outcomes including lower mortality rates (Farmer et al 1991; Shi and Starfield 2001; Shi et al 2003), earlier cancer detection (Roetzheim et al 2000), and better birth outcomes (Nesbitt et al 1997; Vogel and Ackermann 1998). It is widely assumed, but with much less evidence, that where there are more primary care physicians people's access to outpatient medical care also is better (Hicks 1990; Patrick et al 1988). The presumed link between an adequate primary care physician presence and access is a fundamental rationale for the many federal and state provider safety net programs, like the Title VII initiatives that support primary care physician training, the National Health Service Corps which entices physicians to needy areas with financial support for their training expenses, and Medicare's Incentive Payment Program for physicians in underserved areas (Berk, Bernstein, and Taylor 1983; GAO 1995; Grumbach, Vranizan, and Bindman 1997).…”
mentioning
confidence: 99%
“…Many items were commonly used outpatient access-relevant questions from national periodic surveys like the BRFSS 33 and the National Health Interview Survey. 34 We added other items from previous regional surveys and published studies [35][36][37] and included a few new items to address less often queried areas of outpatient access such as whether people found travel to get care is difficult. Satisfaction items were chosen for the range of outpatient-and rural-relevant issues they addressed, like the perceived quality and cost of care and people's satisfaction with their interactions with their providers.…”
Section: Datamentioning
confidence: 99%